An Assessment of Information Services Provision in University Libraries in Accordance with the Commission of University Education (CUE) Guidelines: Selected Libraries in Western Kenya - Nyakweba, Irene; Muwanguzi Bukiwa, Joyce; Sendikadiwa, Eunice; Ratanya, Felicitas (Journal of Information and Knowledge, 2021)
Universities are institutions established to contribute to the social and economic development of a country. The libraries therein enable users to transform the information accessed into valuable knowledge and apply it in research, business and government. While the significance of providing quality information services to users is generally conceded, very little is known as to whether the information services provided by the public university libraries in Western Kenya comply with the Commission of University Education (CUE) standards from the perspective of the staff and users. The purpose of this study is to assess the extent of information services provision in accordance with the CUE guidelines, examine the challenges faced in providing the information services and offer suggestions for improving the services. Descriptive survey research design is adopted in the study. The study was conducted in four public university libraries in the Western region of Kenya targeting undergraduate students, lecturers and library staff. Data was collected through structured questionnaires and interviews, document analysis and observation of the library facilities. Review of Literature was done to examine what has been done on the information service provison and compliance to standards. Data from the questionnaires was quantitatively analysed and the qualitative data from the interviews was transcribed and themes organised and presented based on the responses. It is a poor state of as majority of public university libraries in Kenya are inadequate in provision of information services, allocated budget, facilities, equipment as well as personnel. The challenges cited by majority of respondents indicate that there is inadequate funding and their library budgets do not meet the threshold of 10% of the institution’s operational budget as stipulated by Commission for University Education (CUE) standards, lack enough reference books (31.1 percent), inadequate library space (24.9 percent), slow Internet connection (23.0 percent), lack of Computers (12 percent) poor customer service (3.3 percent) and unfriendly staff (2.5 percent). Suggestions given in the study indicate the need for additional budget for acquisition of additional information resources, recruit additional staff and ensure sustainable service provision. The study concluded that besides adhering to the CUE standards and guidelines in the provision of information services, the libraries need to be proactive in providing user centered services.